2002
DOI: 10.1115/1.1516198
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Progressive Deformities in Adolescent Idiopathic Scoliosis Using a Biomechanical Model Integrating Vertebral Growth Modulation

Abstract: While the etiology and pathogenesis of adolescent idiopathic scoliosis are still not well understood, it is generally recognized that it progresses within a biomechanical process involving asymmetrical loading of the spine and vertebral growth modulation. This study intends to develop a finite element model incorporating vertebral growth and growth modulation in order to represent the progression of scoliotic deformities. The biomechanical model was based on experimental and clinical observations, and was form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 20 publications
3
48
0
Order By: Relevance
“…Following maturation, chondrocytes progress toward hypertrophy and secrete type X collagen, the matrix for the hypertrophic cartilage destined for endochondral ossification [52]. Runx2, a transcription factor that belongs to the Runx family [53], also regulates chondrocyte maturation and terminal differentiation during endochondral bone formation [6][7][8][9][10][11][12][13][14][15][16][17][18][19]54]. Many in vitro studies indicate that Runx2 is a positive regulator that can upregulate the expression of bone matrix genes, including type I collagen, type X collagen, osteopontin, bone sialoprotein (BSP), osteocalcin, and fibronectin [24,[55][56][57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following maturation, chondrocytes progress toward hypertrophy and secrete type X collagen, the matrix for the hypertrophic cartilage destined for endochondral ossification [52]. Runx2, a transcription factor that belongs to the Runx family [53], also regulates chondrocyte maturation and terminal differentiation during endochondral bone formation [6][7][8][9][10][11][12][13][14][15][16][17][18][19]54]. Many in vitro studies indicate that Runx2 is a positive regulator that can upregulate the expression of bone matrix genes, including type I collagen, type X collagen, osteopontin, bone sialoprotein (BSP), osteocalcin, and fibronectin [24,[55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that the different growth rates between the right and the left side of the vertebrae generated the asymmetric growth and wedging of the vertebrae. This feature plays a main role in the progression of the curve [4][5][6][7][8]. Parent et al [9] investigated a large number of scoliotic specimens and found that the vertebral wedging was predominant in the front plane instead of the sagittal plane.…”
Section: Introductionmentioning
confidence: 97%
“…Whether or not the progression of an established scoliotic deformity is secondary to asymmetric loading, correction of the deformity using the principles of Hueter-Volkmann law is possible as long as there is sufficient residual growth. Other studies [20,21] have demonstrated the feasibility of the modeling approach achieving at the same time a complete representation of the scoliotic spine.…”
Section: The Pathomechanism Of Progressionmentioning
confidence: 99%
“…The sensitivity factor b l is determined from experimental data and is considered independent of the external environment. This modeling approach was integrated in beam-type finite element models by simulating the resulting strain increments as thermal loadings or equivalent forces to carry out bone geometrical changes [4,27,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…According to experimental results, Stokes and Laible [27] hypothesized a linear relationship between compressive or tensile stresses and mechanobiological growth rate, in which growth plate stresses perpendicular to the growth plates are acting as mechanical stimuli to bone growth. This modeling approach was integrated in a beam finite element model of the thoracic and lumbar spine to simulate asymmetrical growth of the rib cage and/or vertebrae [27,28,36,37] and in a solid vertebral model to simulate the progression of scoliosis induced by the biomechanical growth modulation [26]. Carter et al proposed a theoretical relationship between bone growth, which incorporated the endochondral growth and ossification, and mechanical loading based on the physiological observations of the ossification of the hand in a 32-month-old child [2,5,6,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%